Analysis of the clinical and epidemiological profile of women with molar pregnancies treated at a mole reference center in brazilian Northeastern between January 2011 to January 2019 (Research, Society and Development, 2020)
The hydatidiform mole (MH) is a gestational trophoblastic disease (DTG) characterized by cell proliferation originating from the placental trophoblastic epithelium in a disorderly manner. Like this, the research aimed to analyze the clinical and epidemiological profile of group of pregnant women attended at a hydatidiform mole reference center in Brazilian northeastern between January 2011 and January 2019. The cross-sectional observational study with a quantitative approach, was based on data from the medical records of 174 patients who had a confirmed histopathological diagnosis for mola or non-mole abortion between 2011 and January 2019. These were divided into two groups: hydatidiform mole, with pregnant women with histopathology confirmed with the disease and absence of hydatiform mole, those that presented remains or abortive material in histopathology. Epidemiological, clinical and laboratory parameters were analyzed between groups. Inferential analysis was applied using Fisher's exact test and chi-square. Of the 174, 66.1% were diagnosed with MH and 33.9% with absence. The profile between both groups of patients was very similar, differing in schooling, outcome and number of consultations, levels of β-hCG. There was a statistical difference between the two groups between occupation, education, parity, outcome, attendance, number of consultations and levels of β-hCG. It is concluded that there is a significant statistical difference between socioeconomic, gynecological and laboratory factors between patients with abortion and hydatidiform mole.